APPLYING BLENDED LEARNING IN HIGHER EDUCATION IN AMBON, INDONESIA: DESCRIPTIVE REPORT FROM GRAMMAR IN WRITTEN DISCOURSE CLASS - Helena Magdalena Rijoly (JURNAL TAHURI, 2021)
This paper is an account on the application of Blended Learning in Higher Education setting in Ambon, Indonesia. The Blended Learning was applied to the Grammar in Written Discourse Class in English Study Program of Faculty of Teachers’ Training Unpatti. The Blended Learning process was supported by the use of three online platforms: Google Classroom, Quizziz and Kahoot. The main purposes of this paper are: to describe the process of applying the blended Learning from planning, preparation, application and evaluation, to describe the challenges of applying the Blended learning for the Lecturer, to describe the challenges of using the Blended learning for the students and to describe the lesson learned and successes from the application of Blended Learning